Analysis and optimization of LN2 two-phase flow in CRAFT NNBI cryopump - Qianxu Wang; Yuanlai Xie; Huihui Hong; Yang Zhu; Fang Wang; Kun Tian; Bin Li (Nuclear Engineering and Technology)
As an important component of Negative ion based Neutral Beam Injector (NNBI), the cryopump mainly provides a suitable vacuum environment for beam generation and transmission. In the paper, Liquid nitrogen (LN2) pipe structure models of two cryopumps were established for simulation and experimental studies. Thermal analysis of the thermal radiation shielding baffle (LN2 cooling) was carried out by Ansys steady-state thermal analysis software, while Fluent was used to simulate the two-phase flow in the LN2 pipeline, then the pressure drops, temperature, velocity, gas-phase volume fraction, and other parameters of the two pipeline structures were analyzed and compared. The simulation results show that the optimized structure B can reduce the pressure drop by 3 bar, the outlet temperature of structure A is 78.8 K, the outlet temperature of structure B is 79.2 K, the temperature difference is 0.4 K. The outlet velocity increases from 2.067 m/s to 4.947 m/s for Structure A, and from 1.096 m/s to 6.614 m/s for Structure B. The experiment results show that the outlet temperature of structure A is 79.4 K, meanwhile the outlet temperature of structure B is 80.1 K, the optimized structure B can reduce the pressure drop about 3 bar.